Assessing Cheese Whey Components for Their Potential to Improve Intestinal Health (P06-097-19). (13th June 2019) - Arbizu-Berrocal, Shirley; Talcott, Susanne; Noratto, Giuliana; Chew, Boon; Talcott, Stephen
Abstract: Objectives: To evaluate the potential of cheese whey bioactive components for intestinal health and barrier function in vitro . Methods: HT29-MTX intestinal globet cells were treated with whey protein isolate (WPI), glycomacropeptides (GMP) and a galacto-oligosacharide rich whey protein isolate (WPI-GOS) followed by challenge with lipopolysaccharides (LPS, 4 µg/ml). Reactive oxygen species (ROS) production was assessed using the 2, 7 dichlorofluorescein diacetate (DCFH-DA) assay. Gene and protein expression of intestinal inflammation biomarkers were also assessed using standard analytical techniques. The effects of WPI, WPI-GOS and GMP on barrier function were assessed on a co-culture (Caco-2/HT29-MTX in a 75/25 ratio, respectively) cell model through the transepithelial electrical resistance (TEER) and apparent permeability (Papp) assays; whereas protein expression of tight junction biomarkers was assessed by Western Blots. Results: WPI, GMP and WPI-GOS did not inhibit cell viability of colon cells within a dose range of 25–100 µg/ml. LPS induced ROS production in HT29-MTX cells up to 1.92 -fold of control and this effect was prevented by WPI, GMP and WPI-GOS (100 µg/ml) that maintained ROS down to levels that were similar to controls not challenged with LPS. GMP protected colon cells at a highest extent against the expression of inflammatory biomarkers (nuclear factor kappa β (NF-kβ), tumor necrosis factor (TNF-α) and toll-like receptor 4 (TLR-4)) on HT29-MTX cells challenged with LPS and maintained NF-kβ and TNF-α at levels similar to untreated control. In addition, GMP improved TEER (1.3-fold of untreated control) and decreased intestinal permeability by 64% in Caco-2/HT29-MTX co-cultures. Finally, these results were accompanied by the upregulation of tight junction proteins (Claudin-1, Claudin-3, Occludin and Zonulin-1) exerted by GMP and WPI at similar levels. Conclusions: WPI, GMP and WPI-GOS protected against ROS production at similar levels. However, GMP protected colon cells against LPS-induced inflammation and improved barrier function with higher potency than WPI and WPI-GOS. These results strongly suggest that cheese whey components may be used by the functional foods industry as ingredients to improve intestinal health with emphasis on GMP as anti-inflammatory ingredient. Funding Sources: BUILD Dairy Program.